1995
DOI: 10.1172/jci117738
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human bone marrow-derived osteoprogenitor cells by osteogenic growth factors.

Abstract: Human bone marrow contains a distinct cell population that expresses bone proteins and responds to transforming growth factor p1 (TGF-,B), but not to hematopoietic growth factors (Long, M. W., J. L. Williams, and K. G. Mann. 1990. J. Clin. Invest. 86:1387-1395. We now report the isolation, characterization, and growth factor responsiveness of these precursors to human osteoblasts and the identification of a human osteoprogenitor cell. Immunological separation of human bone marrow nonadherent low-density (NALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(156 citation statements)
references
References 34 publications
5
145
0
6
Order By: Relevance
“…Moreover, molecular analysis demonstrated a common retroviral integration site in clonogenic hematopoietic cells and osteoprogenitors from each of seven animals studied, establishing a shared clonal origin for these cell types. These findings thus lent considerable credence to the previous work of Long et al [3,4] and established that, at least in the experimental paradigm used by Dominici and colleagues [9], non-adherent bone marrow cells have a >10-fold more robust bone-repopulating activity than do adherent bone marrow stromal cells. Moreover, the findings were also consistent with previous work by Olmsted-Davis et al [10] suggesting the presence of a unique progenitor cell with both hematopoietic and osteoblastic differentiation potential in the non-adherent subset of bone marrow cells.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Moreover, molecular analysis demonstrated a common retroviral integration site in clonogenic hematopoietic cells and osteoprogenitors from each of seven animals studied, establishing a shared clonal origin for these cell types. These findings thus lent considerable credence to the previous work of Long et al [3,4] and established that, at least in the experimental paradigm used by Dominici and colleagues [9], non-adherent bone marrow cells have a >10-fold more robust bone-repopulating activity than do adherent bone marrow stromal cells. Moreover, the findings were also consistent with previous work by Olmsted-Davis et al [10] suggesting the presence of a unique progenitor cell with both hematopoietic and osteoblastic differentiation potential in the non-adherent subset of bone marrow cells.…”
Section: Introductionsupporting
confidence: 78%
“…We found that OCN pos cells isolated using either the antibody we used in our previous work (SC V-19) [14] or the antibody used by Long and colleagues (HT AON-5031) [3,4] identified very similar populations of cells, at least as assessed by flow cytometry and confocal microscopy. While additional studies need to be done further characterizing the cells isolated with the two antibodies, these data do provide some reassurance that the cells identified in our previous work using the SC V-19 antibody are not some type of spurious population staining only with this particular antibody.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations